KONTRIBUSI SEKTOR PARIWISATA TERHADAP REALISASI PENDAPATAN DAERAH DI PROVINSI JAWA TENGAH: PENDEKATAN DATA PANEL - Vinna Dwi Agustina; Sitti Retno Faridatussalam (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
This study aims to analyze the impact of key tourism sector indicators on Regional Original Revenue (PAD) in Central Java Province. The indicators examined include the number of domestic tourist trips, the number of tourist visits and events, the number of hotels and accommodations, as well as the number of restaurants or eateries. A quantitative approach was employed using panel data methods, covering 35 regencies/cities in Central Java Province over a five-year period, resulting in a total of 175 observations. The Fixed Effects Model (FEM) was selected as the most suitable model based on the results of the Hausman test. The model estimation shows that the number of domestic tourist trips, the number of tourist visits and events, and the number of hotels and accommodations have a positive and significant effect on increasing PAD. In contrast, the number of restaurants or eateries does not show a statistically significant effect on PAD. These findings underscore the importance of the tourism sector in enhancing regional fiscal revenue. Optimizing investment and development planning in the tourism sector is expected to strengthen the structure of regional income and support sustainable development agendas at the local level. This study provides empirical contributions by integrating various tourism indicators through a panel data approach to identify the main determinants of PAD at the regency/city level. The findings enrich the body of literature on regional development economics, particularly in data-driven tourism potential management.